2011
DOI: 10.2106/jbjs.j.00474
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bipolar Hemiarthroplasty with Total Hip Arthroplasty for Displaced Femoral Neck Fractures

Abstract: We performed a four-year follow-up of a randomized controlled trial involving 120 elderly patients with an acute displaced femoral neck fracture who were randomized to treatment with either a bipolar hemiarthroplasty or a total hip arthroplasty. The difference in hip function (as indicated by the Harris hip score) in favor of the total hip arthroplasty group that was previously reported at one year persisted and seemed to increase with time (mean score, 87 compared with 78 at twenty-four months [p < 0.001] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
197
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(227 citation statements)
references
References 14 publications
12
197
2
2
Order By: Relevance
“…This is the conclusion in a Cochrane review in which THA in a majority of relatively young and healthy patients had significantly less residual pain and better function at 1, 2, and 4 years after fracture at the cost of increased risk of dislocation and increased surgical time [28], also shown by Hedbeck et al [16]. A cost-effectiveness analysis concluded that it is likely that THA is associated with increased costs in the initial 2-year period, but the longerterm costs favor THA as a result of lower revision rates [4].…”
Section: Discussionsupporting
confidence: 56%
“…This is the conclusion in a Cochrane review in which THA in a majority of relatively young and healthy patients had significantly less residual pain and better function at 1, 2, and 4 years after fracture at the cost of increased risk of dislocation and increased surgical time [28], also shown by Hedbeck et al [16]. A cost-effectiveness analysis concluded that it is likely that THA is associated with increased costs in the initial 2-year period, but the longerterm costs favor THA as a result of lower revision rates [4].…”
Section: Discussionsupporting
confidence: 56%
“…One may suspect that the significant differences in the types of prostheses used might influence comparisons of the functional and quality of life outcomes between the two institutions. However, recent studies showed that there was no significant difference in quality of life in the short-term follow-up when bipolar or THA was implanted in patients with FNFs [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…This did not occur in our series, and the 30-day mortality in another series [20] of more than 7000 patients undergoing THAs for a hip fracture is 2.4%, consistent with our observation. Two randomized trials showed similar mortality rates with THA compared with other treatment options [9,18]. Therefore, it would seem that increasing age and medical comorbidities [16], rather than the magnitude of the surgical procedure, influence mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these considerations, the initial experience with THA for intracapsular fractures suggest rates of dislocation ranging from 2% to 9% [3,4,10,15,23,26]. However, there is an accumulating body of evidence that supports the use of THA in suitable patients, and some studies [4,9,14,18,27] indicate function may be better than after other procedures, particularly hemiarthroplasty. To confirm or refute the reported higher rate of dislocation and recurrent dislocation in patients treated with THAs, we compared patients treated with hemiarthroplasty with patients treated with THA to determine the incidence of first-time dislocation, cumulative risk of dislocation, and influence of demographic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation